APPLICATION OF POLYMERIC NANOPARTICLES IN CANCER DRUG DELIVERY - A REVIEW - D, Shashikanth; V., Gangadharappa H.; J., Sachin (Asian Journal of Pharmaceutical Research and Development, 2014)
Polymeric nanoparticles (PNPs) are defined as particulate dispersions or solid particles with size in the range of 10- 1000nm. There has been a considerable research interest in the area of drug delivery using particulate delivery systems as carriers for small and large molecules. Particulate systems like nanoparticles have been used as a physical approach to alter and improve the pharmacokinetic and pharmacodynamic properties of various types of drug molecules. Polymeric nanoparticles have been extensively studied as particulate carriers in the pharmaceutical and medical fields, because they show promise as drug delivery systems as a result of their controlled and sustained release properties, subcellular size, biocompatibility with tissue and cells. Polymeric nanomaterial’s have the potential to improve upon present chemotherapy delivery methods. They reduce side effects while increasing dosage, have the ability to deliver multiple drugs in one carrier, and offer a sustained release. However, traditional nanomaterial formulations have not produced highly therapeutic formulations to date due to their passive delivery methods and lack of rapid drug release at their intended site. In this paper, we have focused on a few “smart” technologies that further enhance the benefits of typical nanomaterials. Temperature and pH- responsive drug delivery devices were reviewed as methods for triggering release of encapsulating drugs, while aptamers and ligand conjugation were discussed as methods for targeted and intracellular delivery, with emphases on in vivo and in vitro works for each method.